Limited influence of dry deposition of semivolatile organic vapors on secondary organic aerosol formation in the urban plume. Issue 12 (19th June 2013) - Hodzic, A.; Madronich, S.; Aumont, B.; Lee‐Taylor, J.; Karl, T.; Camredon, M.; Mouchel‐Vallon, C.
Abstract : [1] The dry deposition of volatile organic compounds (VOCs) and its impact on secondary organic aerosols (SOA) are investigated in the Mexico City plume. Gas‐phase chemistry and gas‐particle partitioning of oxygenated VOCs are modeled with the Generator of Explicit Chemistry and Kinetics of Organics in the Atmosphere (GECKO‐A) from C3 to C25 alkanes, alkenes, and light aromatics. Results show that dry deposition of oxidized gases is not an efficient sink for SOA, as it removes <5% of SOA within the city's boundary layer and 15% downwind. Dry deposition competes with the gas‐particle uptake, and only gases with fewer than 12 carbons dry deposit while longer species partition to SOA. Because dry deposition of submicron aerosols is slow, condensation onto particles protects organic gases from deposition, thus increasing their atmospheric burden and lifetime. In the absence of this condensation, 50% of the regionally produced mass would have been dry deposited. Key Points: Dry deposition of anthropogenic organic vapors has small effect on regional SOA Dry deposition competes with the uptake of gases to the organic particle phase Neglecting SOA formation leads to underestimation of the lifetime of organics